THE INFLUENCE OF COMPENSATION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE AT PT. RAZZA PRIMA TRANSFORMER MEDAN - Muslih, Muslih; Saragih, Ivan Alghifari (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to test and analyze the influence of compensation and organizational commitment on performance through work discipline directly and indirectly. The approach used in this research is a causal approach. The population in this study were all employees of PT. Razza Prima Transformer Medan. The sample in this study using the Slovin formula consisted of 60 employees. Data collection techniques in this research used documentation, observation and questionnaire techniques. The data analysis technique in this research uses a quantitative approach using statistical analysis using Outer Model Analysis, Inner Model Analysis and Hypothesis Testing. Data processing in this research uses the PLS (Partial Least Square) software program. The results of this research show that directly the influence of compensation, organizational commitment and work discipline has a significant effect on performance, compensation and organizational commitment have a significant effect on work discipline, and indirectly compensation and organizational commitment have a significant effect on performance through work discipline at PT. Razza Prima Transformer Medan